Pengawetan dan Pengolahan Telur pada Kelompok Wanita Tani Kusuma Dewi Dusun Segah Desa Asahduren, Kecamatan Pekutatan, Kabupaten Jembrana - Yudiastari, Ni Made; Suariani, Luh; Suardani, Ni Made Ayu; Janurianti, Ni Made Defy; Bili, Yuminsia Neni; Sundari, Sri Wulan (Abdimas Universal, 2026)
This community service activity aims to improve the knowledge and skills of members of the Kusuma Dewi Women's Farmers Group in preserving and processing eggs to extend their shelf life, increase added value, and open new business opportunities. The activity was carried out through theoretical and practical training covering egg preservation techniques using traditional and modern methods, as well as processing eggs into processed products such as salted eggs and smoked eggs. During the training, group members were trained on everything from selecting quality eggs, hygienic preservation processes, to producing processed products that have market appeal. The community service team also provided assistance in packaging and marketing strategies so that processed egg products would be well received by local consumers and the wider market. The results of the activity showed an increase in the group members' skills in processing and preserving eggs effectively. Group members successfully produced various types of processed eggs that were marketable and had a higher economic value than ordinary fresh eggs. In addition, this activity helped increase the motivation and economic independence of the women's farming group, while also opening up new sustainable business opportunities in Asahduren Village.